2017
DOI: 10.1016/j.canlet.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Regorafenib overcomes chemotherapeutic multidrug resistance mediated by ABCB1 transporter in colorectal cancer: In vitro and in vivo study

Abstract: Chemotherapeutic multidrug resistance (MDR) is a significant challenge to overcome in clinic practice. Several mechanisms contribute to MDR, one of which is the augmented drug efflux induced by the upregulation of ABCB1 in cancer cells. Regorafenib, a multikinase inhibitor targeting the RAS/RAF/MEK/ERK pathway, was approved by the FDA to treat metastatic colorectal cancer and gastrointestinal stromal tumors. We investigated whether and how regorafenib overcame MDR mediated by ABCB1. The results showed that reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 55 publications
2
39
0
Order By: Relevance
“…Our results indicated that the ABCB1-overexpressing SW620/AD300 cells were greater than 80-fold resistant, as compared to the parental SW620 cells, whereas the ABCG2-overexpressing NCI-H460/MX20 cells were greater than 150-fold resistant, compared to the non-resistant parental NCI-H460 cells. As reported previously, the resistance fold (RF) was calculated by dividing the substrate drug IC50 values in the drug-resistant cells by the IC50 values in the parental cells [10,46,58]. The resistant profile of our cells was comparable to the previously published studies [12,59].…”
Section: Discussionsupporting
confidence: 60%
“…Our results indicated that the ABCB1-overexpressing SW620/AD300 cells were greater than 80-fold resistant, as compared to the parental SW620 cells, whereas the ABCG2-overexpressing NCI-H460/MX20 cells were greater than 150-fold resistant, compared to the non-resistant parental NCI-H460 cells. As reported previously, the resistance fold (RF) was calculated by dividing the substrate drug IC50 values in the drug-resistant cells by the IC50 values in the parental cells [10,46,58]. The resistant profile of our cells was comparable to the previously published studies [12,59].…”
Section: Discussionsupporting
confidence: 60%
“…The modified MTT colorimetric assay was used to detect the sensitivity of cells to anticancer drugs in vitro as previously described [19, 22]. The cells were trypsinized and resuspended in a final concentration of 4 × 10 3 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…The vanadate-sensitive ATPase activity of ABCB1 and ABCG2 in crude membranes of High-five insect cells was measured in the presence of voruciclib (0 to 40 µM) by PREDEASY ATPase Kits with modified protocols, as previously described [22, 27]. …”
Section: Methodsmentioning
confidence: 99%
“…Progresses in combination chemotherapy such as FOLFOX, XELOX/CAPOX, FOLFIRI, and therapeutic antibodies against vascular endothelial growth factor (VEGF) and epidermal growth factor receptor (EGFR) have been shown to increase survival time. However, the emergence of multidrug resistance (MDR), accounting for the poor tumor response to antineoplastic agents, has greatly limited the efficacy of chemotherapeutic drugs and finally results in therapy failure in CRC patients [2][3][4]. Due to primary or acquired resistance, many patients either respond poorly to the chemotherapy or respond well initially but experience later tumor relapse and disease progression.…”
Section: Introductionmentioning
confidence: 99%